OFFENDERS, ADULTERESSES, AND MURDERESSES IN AMERICAN LITERATURE: FROM THE COLONIAL TO THE POSTMODERN ERA - Knežević, Jelena; Nikčević Batrićević, Aleksandra (Armenian Folia Anglistika, 2023)
This paper examines American female transgressors from the early colonial period to the late postmodern age and their representations in American literature. Its main aim is to identify the most relevant female offenders from each historical era and analyze how authors portray their characters in each literary work. Furthermore, it offers different insights into the social, cultural, political, and jurisprudential contexts of the murder cases of each female perpetrator under discussion. The paper also compares fiction to non-fiction literary texts and the similarities and differences contributing to a murderess’s standard representation. The representation of American transgresses is highly contingent on the literary genre of the texts, the type of offense, and the socio-cultural, historical, and ideological context of the time. What they have in common is that they murder people closely related to them. The opposing groups are single and double homicide committers, emotionally driven by victimization and vengeance, and emotionless serial killers, whose murder-prone behavior emanates from deviance. On the one hand, true-crime books offer unprecedented and controversial details about murderesses. On the other hand, crime fiction puts them into an imagined context. The most common depictions of female perpetrators are victimized women who suffer in a patriarchal society, romanticized femme fatales, or devilized mental health sufferers.